2014
DOI: 10.1111/gwao.12055
|View full text |Cite
|
Sign up to set email alerts
|

‘I Write Like a Painter’: Feminine Creation with Arts‐Based Methods in Organizational Research

Abstract: Feminine writing and organizational aesthetics are brought together in this paper to sketch a different form of academic production in organizational research that involves arts‐based methods (‘feminine creation’). Feminine creation relates to écriture féminine (Cixous, Irigaray, and Kristeva) and also to peinture féminine (Nancy Spero) and modern choreography (Trisha Brown). Feminine creation responds to the feminist and the aesthetic critique of conventional academic writing and has the potential to challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 51 publications
1
31
0
2
Order By: Relevance
“…By ‘personal style’, we refer to feminine and aesthetic styles of writing, which might help us to challenge the masculine stereotypes of academic writing in rational, disembodied, rigorous and rather distant ways (e.g. Biehl-Missal, 2014; Cixous, 1976; Pullen, 2018). At the same time, embodied writing renders us vulnerable – it ‘violates the writer’ in a patriarchal culture (Pullen, 2018: 124).…”
Section: Methodological Choicesmentioning
confidence: 99%
See 1 more Smart Citation
“…By ‘personal style’, we refer to feminine and aesthetic styles of writing, which might help us to challenge the masculine stereotypes of academic writing in rational, disembodied, rigorous and rather distant ways (e.g. Biehl-Missal, 2014; Cixous, 1976; Pullen, 2018). At the same time, embodied writing renders us vulnerable – it ‘violates the writer’ in a patriarchal culture (Pullen, 2018: 124).…”
Section: Methodological Choicesmentioning
confidence: 99%
“…Research has long shown that female academics continue to battle gendered beliefs and stereotypes in developing sustainable careers (Armenti, 2004; Fotaki, 2013; Johansson and Śliwa, 2013; King, 2008; Pas et al, 2014; Toffoletti and Starr, 2016). In academia, pregnancy is arguably largely considered unprofessional, and maternal bodies are usually abject (Biehl-Missal, 2014; Gatrell, 2014; Kristeva and Goldhammer, 1985; Mäkelä, 2009; Tyler, 2009). Before having children, both authors feared becoming ‘othered’ in academia owing to motherhood, a common fear among mothers-to-be (Nikunen, 2012; Warren and Brewis, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Chia (2014) points towards organizational scholarship embedded in artistic sensitivities and capabilities. Aesthetic forms such as poetry may unearth insights, creativity and enlightenment, help to make sense of organizational complexity, offer fresh insights through embodied and tacit representation, as well as empower individuals, thus contributing to organization studies and management practices (Armitage, 2015; Biehl-Missal, 2015; Cairns, 2002; Knight, 2015; Xing and Liu, 2015). Poetry has been used as a pedagogical approach with cadets at West Point to understand leadership and ethics in various situations (Buskirk et al, 2015), as a reflective stance with health-care practitioners (Lapum et al, 2015), in entrepreneurship (Smith, 2015), and by business educators to develop emotional intelligence (Morris et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Admittedly, even in writing differently, studying (marginalized) experiences remains bound by textual forms, which will always be limited in representing embodied and affective intensities. Arts‐based scholars have therefore argued for the need to also include methodologies that go beyond text, such as visual art, dance, performance art, and music (e.g., Biehl‐Missal, 2015; Leavy, 2017).…”
Section: Writing Differently In Collecting and Analyzing (Ethnographic) Datamentioning
confidence: 99%